Investigation of Kidney Histopathology in Rats Receiving Methamphetamine Simultaneously with Berberine Hydrochloride and Aerobic Exercise - Danial Naghipour; Aref Arminfar; Zahra Sahraneshin Samani; Lida Sepanloo; Hessamedin Babaei; Mohammad Hossein Hasani; Behrooz Yahyaei (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Given the widespread issue of methamphetamine addiction and its damaging effects, coupled with the crucial role of the kidneys in maintaining bodily equilibrium, we chose to undertake this study. Methods: Forty rats were randomly divided into five equal groups: control, methamphetamine, methamphetamine with exercise, methamphetamine with berberine hydrochloride, and methamphetamine with both exercise and berberine hydrochloride. The administration of methamphetamine at a dose of 15 mg/kg intraperitoneally for a duration of 4 days every 12 hours and berberine hydrochloride 100 mg/kg intraperitoneally for a duration of 4 weeks daily has been conducted. Aerobic exercise was performed in the form of running on a rodent treadmill for 8 weeks with moderate intensity. Twenty-four hours following the final exercise and administration of berberine hydrochloride, kidney tissue was extracted and examined under a light microscope, in accordance with the ethics committee's guidelines. Results: In the methamphetamine group, the glomerulus diameter decreased, hyperemia and tissue disorganization occurred, and the cells of the proximal and distal convoluted tubules were atrophied. In the methamphetamine group, with exercise, there was a decrease in diameter in some glomeruli and changes in hyperemia and an increase in the diameter of blood vessels. In the group treated with methamphetamine and berberine hydrochloride, there was a noted shrinkage of glomeruli and an increase in urinary space. In the group receiving methamphetamine, exercise, and berberine hydrochloride, the quantity and size of glomeruli as well as  the spaces between them, were normal and without irregularities. Conclusion: This research demonstrated that both aerobic exercise and berberine hydrochloride can mitigate the damaging histopathological impacts of methamphetamine on the kidney, indicating that their simultaneous use may offer enhanced protective benefits. effect